The Effect of Hydro-Morphology and Habitat Alterations on the Functional Diversity and Composition of Macrophyte Communities in the Large River - Vukov, Dragana; Ilić, Miloš; Ćuk, Mirjana; Igić, Ružica (Frontiers in Environmental Science, 2022)
Macrophyte communities have major role in the functioning of freshwater ecosystems. However, there is gap in knowledge about how natural and anthropogenic hydro-morphological disturbances affect their functional diversity and trait structure, particularly in the temperate large rivers. In this study we investigated the effect of hydro-morphology on functional diversity and trait structure of macrophyte communities in the middle section of the Danube course. We collected macrophyte and environmental data from 947 sampling units in the main river channel and connected side waterbodies. We extracted data on 18 traits with 65 trait states and calculated seven functional diversity metrics and cumulative weighted means of trait states (CWMs). We applied redundancy analysis (RDA) to investigate the response of functional diversity metrics to the environmental variables, and Variation Partitioning to determine whether natural, or anthropogenic subset of hydro-morphological factors is more important predictor of functional diversity. To relate CWMs and environmental variables, we performed RLQ and fourth-corner analysis, followed by false discovery rate procedure. Hydro-morphological variables explained 36.7% of the variability in the functional diversity metrics. Combined effect of two subsets of environmental variables explained largest part of the variability in functional diversity metrics. Six associations between traits and environmental variables were found. We found that functional diversity metrics indicate prevailing ecological processes, from environmental to biotic filtering, along the natural—anthropogenic hydro-morphological gradient. We concluded that functional diversity metrics are potentially useful tools in the identification of the causes of ecological degradation, and could be applied in river bioassessments and management.